Character Education Values of Boarding School in the Short Film Inthiq Rasmiyyatan! - Wanda Choirunisa; Rifa Mazin Aqillah; Najwa Rifaron; Rohanda Rohanda (Universitas Negeri Semarang, 2025)
Character Education values are positive values that are instilled in society, one of which is in the film Inthiq Rasmiyyatan! The purpose of this research is to find character education values in the boarding school in the film Inthiq Rasmiyyatan! because many educational values are instilled in this film. The researcher implements structuralism theory that looks at the intrinsic elements in literary works with educational values. The type of research used is qualitative research with data collection techniques using free listening techniques. The data analysis used hermeneutic technique. The results of the research found that there are educational values in the form of hard work, curiosity, discipline, honesty, environmental care, social care, friendship, and respect for achievement. From this research, readers can find out the caracter education value of boarding school in the short film Inthiq Rasmiyyatan!